A PET protective film preparation process

By using plasma treatment or electroless coating technology to form the wear-resistant layer during the preparation of PET film, the problems of poor adhesion and insufficient wear resistance of PET protective film are solved, and its application performance in the field of composite film is significantly improved.

CN119734467AInactive Publication Date: 2025-04-01KUNSHAN XINBOHAO THIN FILM ELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411970952.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing PET protective film has poor adhesion and insufficient wear resistance, making it difficult to firmly combine with other materials, which limits its application in the field of composite films.

Method used

In the preparation process of PET film, plasma treatment or electroless coating technology is used to form a uniform wear-resistant layer on the surface of the film to improve adhesion and wear resistance.

Benefits of technology

It effectively improves the adhesion and wear resistance of PET protective film, broadens its application range in the field of composite films, and improves the service life and stability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119734467A_ABST
    Figure CN119734467A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of protective film preparation, and specifically relates to a PET protective film preparation process, which uses PET resin in a specific molecular weight range, and through the process steps of accurately controlling the drying temperature, optimizing the mixing steps of ingredients, accurately controlling the melting temperature of the extruder, surface treatment, multi-layer composite, slitting, performance testing, and improving the packaging method, the prepared PET protective film has excellent wear resistance, good mechanical strength and stability. The present invention is suitable for various application scenarios with high requirements for surface wear resistance, such as electronic screen protection, automotive interior, etc., and can effectively improve the service life of the product and user experience. The present invention has a reasonable process flow, moderate equipment requirements, is easy to industrialize, and has broad market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of protective film preparation, and in particular relates to a PET protective film preparation process. Background Art

[0002] PET, or polyethylene terephthalate, is a highly crystalline polymer with excellent wear resistance, electrical insulation, flame retardancy, heat aging resistance and low water absorption. Therefore, PET protective film with special protective properties is widely used in electronic products such as computers, digital cameras and mobile phones, and is attached to their surfaces to protect them from damage and pollution.

[0003] However, during use, PET film has some technical problems, mainly including poor adhesion. When PET film is combined with other materials, due to its low surface energy, it has poor adhesion and is difficult to firmly combine with other laminated materials, limiting its application in the field of composite films; insufficient wear resistance: PET film is susceptible to mechanical wear during application, which reduces the service life of the product, especially in high friction environments. Summary of the invention

[0004] (1) Technical issues to be solved

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a PET protective film preparation process. By adopting plasma treatment or chemical plating technology during the preparation process, a uniform wear-resistant layer is formed on the surface of the PET film to increase the wear resistance and improve the adhesion.

[0006] (2) Technical solution

[0007] In order to solve the above technical problems, the present invention provides a PET protective film preparation process, comprising the following steps:

[0008] S1. Raw material preparation: select high-purity PET resin, nano-silicon dioxide (after special surface modification treatment), and other additives;

[0009] S2, pretreatment: drying the PET resin to reduce the moisture content; surface modification of nano-silicon dioxide to improve its dispersibility in the PET substrate;

[0010] S3, mixing ingredients: using a high shear mixer to mix PET resin, modified nano-silica and other additives to ensure that the nanoparticles are evenly dispersed in the PET matrix;

[0011] S4, melt extrusion; melt extruding the mixture through an extruder, using a specially designed extruder screw and die head;

[0012] S5, casting and cooling: the melt is cast into a film through a casting head and quickly cooled by a cooling roller;

[0013] S6. Surface treatment: using plasma treatment or chemical coating technology to form a uniform wear-resistant layer on the surface of the PET film;

[0014] S7, multi-layer lamination: laminating the treated PET film with the base film or the multi-layer functional film through a hot pressing lamination process;

[0015] S8, cutting: accurately cutting the laminated PET protective film;

[0016] S9, inspection: various performance tests are carried out on the cut PET protective film;

[0017] S10, packaging: packaging the qualified PET protective film.

[0018] Furthermore, the step S1 includes selecting a PET resin having an average molecular weight in the range of 20,000 to 30,000.

[0019] Furthermore, in the S2 pretreatment step, the temperature of the drying treatment of the PET resin is controlled between 100°C and 150°C.

[0020] Furthermore, in the step of mixing the ingredients, the dispersion concentration of the nano-silicon dioxide is 5% to 15%.

[0021] Furthermore, in the melt extrusion step, the melt temperature of the extruder is set to 260°C to 320°C.

[0022] Furthermore, in the surface treatment step, the wear-resistant layer formed has a thickness of 0.5 micrometers to 10 micrometers.

[0023] Furthermore, in the multi-layer composite step, the bottom film is made of polyethylene material.

[0024] Furthermore, the slitting step includes laser cutting technology to ensure that the cutting accuracy reaches ±0.1 mm.

[0025] Furthermore, the inspection step includes testing the hardness, adhesion and weather resistance of the wear-resistant layer.

[0026] Furthermore, the packaging step uses anti-static bags and moisture-proof boxes to ensure stable quality of the product during transportation and storage.

[0027] Beneficial Effects

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] By improving each preparation step, the technical problems of the existing PET film in terms of adhesion, wear resistance, weather resistance and preparation process are solved. The preparation process effectively improves the comprehensive performance of the PET protective film and broadens its application range in different fields. By adopting the present invention, a PET protective film product with excellent mechanical properties, stability and reliability can be obtained, while improving production efficiency and reducing production costs, bringing significant economic and social benefits to related industries.

[0030] The preparation process of the present invention optimizes the adhesion of the PET protective film, and ensures the uniform dispersion of the nanoparticles in the PET substrate through special pretreatment and ingredient mixing steps, thereby significantly improving the adhesion of the film to other materials. This improvement helps to improve the stability of the composite film and provides a better solution for applications in the fields of packaging, electronics, etc.

[0031] The present invention adds the test of hardness, adhesion and weather resistance of the wear-resistant layer, which fully guarantees the reliability and stability of product performance. This improvement helps users to better evaluate and use the product and reduces the risk of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the preparation process of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] See also Figure 1 , the present invention provides the following embodiments:

[0035] A PET protective film preparation process comprises the following steps:

[0036] Step 1: Raw material preparation

[0037] High-purity PET resin (average molecular weight of 25,000), nano-silica (specially surface-modified to enhance its dispersibility in the PET matrix), and other additives such as antioxidants and UV stabilizers were selected.

[0038] Step 2: Preprocessing

[0039] The PET resin was placed in a dryer for drying at 120°C for 4 hours to reduce the moisture content to below 0.01%. At the same time, the nano-silicon dioxide was treated with a surface modifier to improve its dispersibility and compatibility in the PET substrate.

[0040] Step 3: Mix the ingredients

[0041] Use a high shear mixer to mix the dried PET resin, modified nano-silica and other additives. During the mixing process, the dispersion concentration of nano-silica is maintained at 10% to ensure that it is evenly dispersed in the PET substrate.

[0042] Step 4: Melt Extrusion

[0043] The mixture was melt extruded through an extruder, the extruder model was TDS-45, with specially designed screw and die to optimize the fluidity of the melt and extrusion efficiency. The temperature during the melt extrusion process was set at 280°C and the screw speed was 300 rpm.

[0044] Step 5: Casting and Cooling

[0045] The melt is cast into a film through a casting head, and the thickness of the film is controlled at 100 microns. The cast film is immediately cooled quickly by a cooling roller at a temperature of 20°C to ensure that the film solidifies quickly and remains flat.

[0046] Step 6: Surface Preparation

[0047] Plasma treatment technology is used to form a uniform wear-resistant layer on the surface of the PET film. The treatment power is 2kW and the treatment time is 30 seconds to form a wear-resistant layer with a thickness of 5 microns.

[0048] Step 7: Multiple layers

[0049] The treated PET wear-resistant film was compounded with the bottom polyethylene film by a hot pressing process, with a compounding temperature of 150°C, a pressure of 0.5 MPa, and a time of 10 seconds.

[0050] Step 8: Cutting

[0051] The laminated PET protective film is sent to the slitting machine for slitting. Laser cutting technology is used to ensure that the cutting accuracy reaches ±0.1 mm to meet the needs of different specifications.

[0052] Step 9: Inspection

[0053] The slit PET protective film is subjected to various performance tests, including the hardness of the wear-resistant layer, adhesion, weather resistance and mechanical strength, to ensure that the product meets the predetermined quality standards.

[0054] Step 10: Packaging

[0055] The qualified PET protective film is rolled up on an anti-static tube and packed in a moisture-proof box to ensure the stable quality of the product during transportation and storage.

[0056] In order to improve the dispersibility of nano silicon dioxide in the PET substrate, this embodiment also uses ultrasonic dispersion technology. In the batching and mixing step, the mixture is first processed by an ultrasonic dispersion system before entering the high shear mixer. The system can effectively break up the nanoparticles before they agglomerate, thereby ensuring that the nanoparticles are evenly dispersed at the submicron level in the PET substrate. The frequency of the ultrasonic dispersion system is set to 20kHz, and the processing time is 10 minutes.

[0057] In addition, in order to further improve the weather resistance and adhesion of the wear-resistant layer, this embodiment uses a special chemical coating technology in the surface treatment step. After the plasma treatment, a chemical coating containing ultraviolet absorbers and antioxidants is coated on the surface of the PET film by roller coating or spraying. This coating can not only improve the weather resistance of the wear-resistant layer, but also enhance its adhesion to the PET substrate, thereby maintaining stable performance during long-term use.

[0058] In the multi-layer composite step, in order to further improve the physical properties of the composite film, this embodiment also uses an online detection system to monitor the temperature and pressure during the composite process. Through real-time feedback and adjustment, accurate control of the composite process is ensured, and quality problems of the composite film caused by temperature and pressure fluctuations are avoided. In addition, the multi-layer composite technology is adopted, and by introducing other functional layers, such as barrier layers, heat sealing layers, etc., the practicality and scope of application of the composite film are further improved.

[0059] In the product inspection stage, in addition to conventional physical and chemical performance tests, this embodiment also adds environmental simulation tests. By simulating different environmental conditions, such as high temperature, high humidity, ultraviolet radiation, etc., the durability and reliability of the wear-resistant layer in different environments are evaluated. These tests ensure the performance of the product in real application scenarios, improve user satisfaction and product market competitiveness.

[0060] Finally, in order to ensure product traceability and quality monitoring, this embodiment introduces a QR code tracking system at the packaging stage. Each product package has a unique QR code, and users can obtain information such as the product's production date, batch number, and inspection report by scanning the QR code, which is convenient for users and enhances the transparency of product quality.

[0061] Through these additional process steps and technical improvements, this embodiment further improves the overall performance and quality of the highly wear-resistant PET protective film and meets higher standard application requirements.

[0062] Through the above steps, the prepared PET protective film has excellent wear resistance, good mechanical strength and stability, and can be widely used in occasions requiring high surface wear resistance.

[0063] Furthermore, step 1 includes selecting a PET resin with an average molecular weight in the range of 20,000 to 30,000. Specifically, the present embodiment selects a PET resin with a uniform molecular weight distribution and an average molecular weight of 25,000 ± 500. By precisely controlling the molecular weight range, the thermal stability and mechanical strength of the PET protective film are effectively improved. Specifically, GPC (gel permeation chromatography) is used to perform molecular weight analysis on the PET resin to ensure that its molecular weight distribution index (Mw / Mn) is less than 2.0. This high-quality PET resin exhibits better fluidity and formability during melt extrusion, which helps to prepare a smooth, defect-free film. In addition, high thermal stability means that the film is not easily degraded during high-temperature processing, ensuring the stability of the product in a high-temperature environment.

[0064] Furthermore, in the S2 pretreatment step, the temperature of the drying treatment PET resin is controlled between 100°C and 150°C. The drying process is carried out in a drying chamber, and the temperature is precisely controlled at 120°C ± 2°C to ensure that the moisture content is less than 0.02%. A dryer with an automatic temperature control system is used, which can monitor and adjust the drying temperature in real time to avoid unstable moisture content caused by temperature fluctuations. By strictly controlling the drying temperature, the moisture in the PET resin is effectively reduced, and bubbles and streaks are prevented from being generated during the melt extrusion process, thereby improving the transparency and mechanical properties of the film.

[0065] Furthermore, in the step of mixing the ingredients, the dispersion concentration of nano silicon dioxide is 5% to 15%. A twin-screw extruder is used for mixing the ingredients, and the extruder has a special mixing section design, which can achieve a more efficient mixing effect. During the mixing process, PET resin, nano silicon dioxide and other additives are fed into the extruder at the same time according to a predetermined ratio, and the uniform dispersion of nano particles is achieved through the action of high temperature and shear force. In addition, a dynamic mixer is used to further ensure the full mixing of filler and resin. Through these measures, the wear resistance and mechanical strength of the prepared film have been significantly improved.

[0066] Furthermore, in the melt extrusion step, the melt temperature of the extruder is set to 260°C to 320°C. The melt temperature of the extruder is strictly controlled within a very narrow range, i.e., 280°C±5°C. To this end, an extruder with a precise temperature control system is used, which can monitor the temperature of the extruder in real time and make fine adjustments when necessary. By precisely controlling the melt temperature, it is ensured that the PET resin reaches the optimal melt state during the extrusion process, thereby ensuring the uniformity and consistency of the film. In addition, the appropriate melt temperature helps to reduce energy consumption and improve production efficiency.

[0067] Furthermore, in the surface treatment step, the thickness of the wear-resistant layer formed is 0.5 micrometers to 10 micrometers. This embodiment adopts plasma treatment technology. The plasma treatment process is carried out in a vacuum chamber, and the formation of the wear-resistant layer is optimized by adjusting the plasma treatment power, treatment time and pressure. For example, in this embodiment, the plasma treatment power is set to 2kW, the treatment time is 60 seconds, and the pressure is 0.1MPa. This treatment method makes the bond between the wear-resistant layer and the PET substrate more firm, and at the same time improves the weather resistance and scratch resistance of the wear-resistant layer.

[0068] Furthermore, in the multi-layer composite step, the bottom film is made of polyethylene material. It can ensure the close bonding between the composite layers. The selected bottom film material is polyethylene (PE), which has good flexibility and heat sealing properties. During the composite process, uniform bonding between the composite layers is achieved by controlling the hot pressing temperature, pressure and time. For example, the hot pressing temperature is set to 150°C, the pressure is 0.6MPa, and the time is 15 seconds. This composite process ensures the stability of the multi-layer composite film while providing good barrier properties and mechanical strength.

[0069] Furthermore, the slitting step includes laser cutting technology to ensure that the cutting accuracy reaches ±0.1 mm. In the slitting step, laser cutting technology is used, which can provide high-precision cutting effects. In this embodiment, the accuracy of the laser cutting machine is set to ±0.1 mm, which can meet the requirements of products of different specifications. Through the computer control system, precise control of the cutting process is achieved, including parameters such as cutting speed, power and frequency. In addition, an automatic deviation correction system is used to ensure accuracy and stability during the cutting process. These measures ensure the dimensional consistency of the product during the slitting process and reduce the scrap rate.

[0070] Furthermore, the inspection step includes testing the hardness, adhesion and weather resistance of the wear-resistant layer. This embodiment adds multiple performance tests during the product inspection stage. In addition to conventional physical and chemical performance tests, it also includes a wear-resistant layer hardness test (using a pencil hardness test method), an adhesion test (using a cross-cutting method) and a weather resistance test (using a xenon lamp aging test). Through these tests, the durability and reliability of the wear-resistant layer in different environments are evaluated. In addition, an efficient data analysis system is used to perform statistical analysis on the test results to ensure that the product meets the predetermined quality standards.

[0071] Furthermore, the packaging step uses antistatic bags and moisture-proof boxes to ensure the stable quality of the product during transportation and storage. The product is wound on an antistatic tube and packed in a moisture-proof box with a sealing strip. Each box is equipped with a desiccant to absorb possible moisture. In addition, the box is affixed with a clear product information label, including product name, specifications, production date, batch number, etc., for easy tracking and identification. This packaging method ensures the stable quality of the product during transportation and storage, and reduces quality problems caused by environmental factors.

[0072] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.

Claims

1. A PET protective film preparation process, comprising the following steps: S1. Raw materials preparation; Select high-purity PET resin, nano-silicon dioxide (specially surface-modified), and other additives; S2, pretreatment: drying the PET resin to reduce the moisture content; surface modification of nano-silicon dioxide to improve its dispersibility in the PET substrate; S3, mixing ingredients: using a high shear mixer to mix PET resin, modified nano-silica and other additives to ensure that the nanoparticles are evenly dispersed in the PET matrix; S4, melt extrusion; melt extruding the mixture through an extruder, using a specially designed extruder screw and die head; S5, casting and cooling: the melt is cast into a film through a casting head and quickly cooled by a cooling roller; S6. Surface treatment: using plasma treatment or chemical coating technology to form a uniform wear-resistant layer on the surface of the PET film; S7, multi-layer lamination: laminating the treated PET film with the base film or the multi-layer functional film through a hot pressing lamination process; S8, cutting: accurately cutting the laminated PET protective film; S9, inspection: various performance tests are carried out on the cut PET protective film; S10, packaging: packaging the qualified PET protective film.

2. The process for preparing the PET protective film according to claim 1, characterized in that: The step S1 includes selecting a PET resin having an average molecular weight in the range of 20,000 to 30,000.

3. The process for preparing the PET protective film according to claim 2, characterized in that: In the S2 pretreatment step, the temperature of the drying PET resin is controlled between 100°C and 150°C.

4. The process for preparing the PET protective film according to claim 3, characterized in that: In the step of mixing the ingredients, the dispersion concentration of the nano silicon dioxide is 5% to 15%.

5. The process for preparing the PET protective film according to claim 4, characterized in that: In the melt extrusion step, the melt temperature of the extruder is set to 260°C to 320°C.

6. The process for preparing the PET protective film according to claim 1, characterized in that: In the surface treatment step, the wear-resistant layer formed has a thickness of 0.5 micrometer to 10 micrometers.

7. The process for preparing the PET protective film according to claim 6, characterized in that: In the multi-layer composite step, the bottom film is made of polyethylene material.

8. The process for preparing the PET protective film according to claim 7, characterized in that: The slitting step includes laser cutting technology to ensure a cutting accuracy of ±0.1 mm.

9. The process for preparing the PET protective film according to claim 8, characterized in that: The inspection steps include testing the hardness, adhesion and weather resistance of the wear-resistant layer.

10. The process for preparing the PET protective film according to claim 9, characterized in that: The packaging steps described use anti-static bags and moisture-proof boxes to ensure stable quality of the product during transportation and storage.